2015
DOI: 10.17957/tpmj/15.2990
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Cardiac Diseases; During Pregnancy and Its Feto-Maternal Outcome

Abstract: The objective of this study was to find the prevalence of cardiac disease among pregnant females and its impact on feto-maternal outcome. Study Design: Descriptive case series. Setting: Cardiology department Gulab Devi Chest Hospital Lahore Duration: April 2013 to April 2014. Patients & Methods: All pregnant females with cardiac disease at any gestation with booked or un-booked statutes were included in this study. Patients were admitted for thorough evaluation and investigations. Labor was monitored intensive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…5 However, our result was high in comparison to studies conducted in other parts of Pakistan where it has been reported as 5.7% and 14.2%. 3,11 This may be an incidental finding or there may be a paradigm shift in the type of disease. We need more studies and research to find out the causes of higher rate of cardiomyopathy in this part of the world.…”
Section: Discussionmentioning
confidence: 99%
“…5 However, our result was high in comparison to studies conducted in other parts of Pakistan where it has been reported as 5.7% and 14.2%. 3,11 This may be an incidental finding or there may be a paradigm shift in the type of disease. We need more studies and research to find out the causes of higher rate of cardiomyopathy in this part of the world.…”
Section: Discussionmentioning
confidence: 99%